Določitev števila aktiviranih trombocitov s protitelesi za aktivirani fibrinogen in selektin-P pri bolnikih z esencialno trombocitemijo in vpliv antiagregacijskih zdravil - Zver, Samo (Zdravniški vestnik, 2004)
Background. Essential thrombocythemia (ET) is a chronic myeloproliferative disease with a platelet count within the range of 400-2000 x 10 9/L. Higher percentage of platelets in the circulation of patients with ET express also activation markers on their membranes. Two of such markers are P-selectin and activated fibrinogen on platelet membranes. Because of frequent thrombembolic and also bleeding related complications, treatment of ET is mandatory. Patients whose platelet count is less than 1000 x 10 9/L and who did not suffer any thrombembolic complication during the course of the disease, are ussually treated with an antiaggregation drug, acetylsalicylic acid 100 mg/daily orally. Clopidogrel is an adenosyn-di-phosphate (ADP) receptor antagonist in platelets. There is no routine clinical data about clopidogrel treatment in the patients with ET and only sporadic case reports can be find in the literature. Patients and methods. In our clinical study we compared antiaggregational effects of acetylsalicylic acid and clopidogrel, by measuring the P-selectin level and activated fibrinogen expression on plateletmembranes. There were 35 ET patients included, within the age range between 21 and 78 years and with platelet counts within 451-952 x 10 9/L. Noneof the patients did suffer any thrombembolic complication during the course of the disease. During the sequential 14 day periods, patients receivedacetylsalicylic acid 100 mg/daily orally, followed by clopidogrel 75 mg/daily orally and ultimativelly, together acetylsalicylic acid 100 mg/daily orally plus clopidogrel 75 mg/daily orally. After each fourteen days period the level of P-selectin and activated fibrinogen activated platelets were determined with monoclonal antibodies on flow cytometer. Statistical evaluation was calculated on the difference of average values between the two small, independent pair groups with the t-test. (Abstract truncated at 2000 characters).
Keywords: Aspirin; Fibrinogen; Flow Cytometry; Platelet Activation; Platelet Aggregation Inhibitors; Platelet Count; Pretočna citometrija; P-Selectin; P-selektin; Thrombocythemia, Hemorrhagic; Trombocit, aktivacija; Trombocitemija hemoragična; Trombociti, štetje; Trombociti, zlepljenje, inhibitorji